A Comparative Analysis of Uplift Modeling and Reinforcement Learning in AI-Driven Decision Optimization - Huzaifa Fahad Syed (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive comparative analysis of two prominent approaches in AI-driven decision optimization: Uplift Modeling and Reinforcement Learning (RL). We explore the fundamental principles, methodologies, and applications of each technique, highlighting their respective strengths and limitations in various decision-making scenarios. Uplift Modeling is examined for its effectiveness in measuring the causal impact of interventions, particularly in marketing and customer segmentation, while Reinforcement Learning is discussed for its adaptability and continuous learning capabilities in dynamic environments. The article delves into the key components of RL systems and their applications in real-time campaign adjustments, personalized recommendations, ad bidding strategies, and chatbot optimization. A detailed comparison is provided, covering aspects such as decision-making scenarios, data requirements, scalability, and performance metrics. Furthermore, the article explores potential synergies between Uplift Modeling and RL, proposing hybrid approaches and identifying future research directions. This article aims to provide researchers and practitioners with a comprehensive understanding of these techniques, their integrative potential, and their implications for the future of AI-driven decision optimization across various industries.